2018
DOI: 10.1177/1542305018773698
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Self-Reported Resilience of APC Chaplains

Abstract: Approximately 5000 members of the Association of Professional Chaplains were surveyed using the Professional Quality of Life instrument in order to assess levels of Compassion Satisfaction and Compassion Fatigue and its associated subscales, Burnout and Secondary Traumatic Stress; 1299 surveys were completed. The most significant finding of this study is that Board Certified Chaplains have remarkably low scores of Burnout and Secondary Traumatic Stress and significantly high levels of Compassion Satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 2 publications
2
8
0
Order By: Relevance
“…In the present research participants reported a strong sense of fulfillment in relation to the opportunity afforded by their work to help others negotiate difficult experiences in their lives (see also, O'Callaghan et al, 2020;Yu et al, 2021). Similarly, the findings of negative relationships between compassion satisfaction and the negative measures of burnout and secondary traumatic stress, on the other hand, replicates previous research findings (Hotchkiss & Lesher, 2018;Oliver et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the present research participants reported a strong sense of fulfillment in relation to the opportunity afforded by their work to help others negotiate difficult experiences in their lives (see also, O'Callaghan et al, 2020;Yu et al, 2021). Similarly, the findings of negative relationships between compassion satisfaction and the negative measures of burnout and secondary traumatic stress, on the other hand, replicates previous research findings (Hotchkiss & Lesher, 2018;Oliver et al, 2018).…”
Section: Discussionsupporting
confidence: 88%
“…The purpose of the current research is to examine the relationship between self-care practices and professional quality of life (ProQOL, Stamm, 2010) in Australian chaplains. A body of research investigating ProQOL has found negative relationships between compassion satisfaction and the stress measures of burnout and secondary traumatic stress (Alkema et al, 2008;Hotchkiss & Lesher, 2018;Oliver et al, 2018). We aim to replicate these findings; therefore, the following hypothesis is advanced:…”
Section: Research Hypothesesmentioning
confidence: 91%
See 1 more Smart Citation
“…Acute spiritual distress (loss of faith) was rare (9.3%), but one-third of the participants experienced Distress from Theodicy and a majority (61%) reported feeling worn out in the past 3 months. Other studies of healthcare chaplains suggest a low prevalence of burnout (Flannelly et al, 2005;Oliver et al, 2018;Taylor et al, 2006;Yan & Beder, 2013). The higher proportion of chaplains reporting distress in the present study may be due to their work in PC; however, a chaplain's exposure to death did not predict increased Professional Distress or Distress from Theodicy.…”
Section: Discussionmentioning
confidence: 97%
“…The potential for decreased empathy within patient-clinician encounters as a result of an imbalance between stress and coping strategies may specifically concern professional PC chaplains. Existing research suggests potentially low levels of distress among chaplains (Flannelly et al, 2005; Oliver et al, 2018; Taylor et al, 2006; Yan & Beder, 2013) and potentially a wider range of coping strategies employed by chaplains compared with nurses (Ekedahl & Wengstrom, 2008); however, researchers have not specifically examined the distress levels of chaplains in PC or their self-care practices.…”
Section: Introductionmentioning
confidence: 99%